Left atrial myxoma: two sides of the same coin. (January 2015) - Pergolini, Amedeo; Zampi, Giordano; Sbaraglia, Fabio; Musumeci, Francesco
Abstract : In this clinical picture we present two cases of left atrial myxoma that differed very much in their clinical presentation.